Coating of Crystalline BaTiO3 Layer on Ni Nanoparticles for Multilayer Ceramic Capacitor Electrode. Issue 10 (16th September 2020) - Zhang, Jiameng; Hao, Yanan; Li, Haihong; Dai, Qionglin; Guo, Limin
Abstract : The base‐metal electrode (BME) is widely applied in multilayer ceramic capacitors (MLCCs) to replace the Pd/Ag electrode, whereas the oxidation and low shrinkage temperature during sintering is difficult to be resolved in nanosized electrode powders. Herein, a facile two‐step route for the fabrication of the crystalline BaTiO3 (BT) layer on Ni nanoparticles is developed. The amorphous BT layer is first coated on Ni nanoparticles by a normal precipitation method. Then, the as‐prepared Ni@BT powders are hydrothermally treated at alkaline conditions to facilitate the crystallization of the coating layer. Due to the dense and uniform crystalline BT layer, the Ni@BT powders show significantly enhanced sintering and antioxidation performance, which provides a high‐performance electrode for BME MLCC. Abstract : A two‐step fabrication route is developed to fabricate the crystalline BaTiO3 (BT) layer on Ni nanoparticles. The prepared coating layer is dense, uniform, and highly continuous, which effectively protects the Ni cores. Moreover, the crystalline BT‐coated Ni nanoparticles show excellent antishrinkage and antioxidation properties, which serve as high‐performance electrode material for base‐metal electrode (BME) multilayer ceramic capacitors (MLCC).